Populärkulturforschung - Maase, Kaspar (Edition Kulturwissenschaft, 2019)
Popular entertainment and entertainment are considered essentially aesthetic phenomena. But is there a specific "aesthetics of the popular"? And how can mass arts affect the development of worldviews and identity orientations in a problematic way? Kaspar Maase focuses on the "mainstream" of mass arts and their everyday usage practices. In his study, he develops an understanding of popular culture as a network of practical interactions between people, texts, things, contexts, and situations, thus providing basic orientations for empirical research in a variety of disciplines. Populäre Unterhaltung und Vergnügung gelten als wesentlich ästhetische Phänomene. Doch gibt es eine spezifische »Ästhetik des Populären«? Und inwiefern können Massenkünste die Ausbildung von Weltsichten und Identitätsorientierungen auf problematische Weise beeinflussen? Kaspar Maase nimmt den »Mainstream« der Massenkünste und dessen alltägliche Nutzungspraktiken in den Fokus. In seiner Studie entwickelt er ein Verständnis von Populärkultur als Netz praktischer Interaktionen zwischen Menschen, Texten, Dingen, Kontexten und Situationen und bietet damit grundlegende Orientierungen für empirische Forschung in einer Vielzahl von Disziplinen.